Comparison of the Frequency of Wound Infection between Sub-cuticular Stitches Versus Interrupted Mattress Sutures after Cesarean Section - Saba Nadeem, Shakila Yasmin, Naila Shabbir, Ayesha Javed, Shaheera Hussain, Sara Reza (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To compare the frequency of wound infection between subcuticular stitches versus interrupted mattress sutures after cesarean section. Setting: Obstetrics & Gynecology Department, Bahawal Victoria Hospital, Bahawalpur. Study duration: 21st July 2019 to 20th December 2020 Study design: Randomized controlled Clinical trial Materials & Methods: In this clinical trial study, A sum-total of 60 women, 18-40 yrs of age, scheduled for planned elective cesarean section through Pfannenstiel incision were enrolled. In Group I women, subcuticular sutures were placed while in group II women, interrupted mattress sutures were placed. All women were discharged on tablet Augmentin 1gram x twice a day for 7 days at which wound infection was noted. Results: The mean age of women in group I was 27.60 ± 5.16 years and was 27.40 ± 3.99 years in group II. My study has shown the wound infection in group I (sub-cuticular stitches) as 01 (3.33%) and in group II (interrupted mattress sutures) as 08 (26.67%) respectively with p-value of 0.011. Conclusion: The inference from my study shows that the wound infection after cesarean section is less after sub cuticular stitches as compared to interrupted mattress sutures.